STUDY OF ZINC-BOROPHOSPHATE GLASSES - Altaf, M.; Chaudhry, M. A.; Naz, Kishwar (Journal of Research (Science), 2004)
Zinc-borophosphate glasses having a mole % composition, 30 ZnO - xB2O3 - (70-x) P2O5 were prepared by using the melt quench technique. The quantity x had values of 10-40mole %. The mass density of these glasses was found to be in the range of 2.4912 to 3.0142 g cm-3. The oxygen packing density and molar volume were estimated to lie in the range 192.385-286.026 g litre-1 and 46.78–31.46cm3 respectively. The absorption spectra of these glasses were recorded in the range 190 to 1100nm. No sharp edges were found in the optical spectra, which confirm the amorphous nature of these glasses. The optical band gap energies were found to be in the range 2.40-3.00 eV. It was found that optical band gap energy increases with increasing concentration of P2O5. The extent of band tailing was worked out from the Urbach plots, which show an exponential dependence of absorption coefficients on photon energies.